SENTIMENT OF INDOVAC VACCINE LAUNCH NEWS ON DETIK.COM USING DISCOURSE NETWORK ANALYSIS - Iqbal Al Khazim; Kayla Nur Alfia Kani; Olly Aurora (Journal of Digital Media Communication, 2023)
This study aims to determine the sentiment of the news of the domestically produced IndoVac Vaccine launch. The pros and cons sentiments of Detik.com's coverage were analyzed using Discourse Network Analysis (DNA) and network visualization using Visone software. The study results are based on news related to the IndoVac vaccine from September 3 to November 30, 2022; there are 50 news stories with 193 statements from 33 Actors. Information, Policy, and Education categories were found, with 93% positive and 7% negative statements. The influence of the IndoVac Vaccine makes social media users more careful in digging up information to understand media coverage, especially regarding the IndoVac vaccine.